Conveying troublesome concepts: Using an open-space learning activity to teach mixed-methods research in the health sciences. Issue 2 (July 2019) - Johnson, Rebecca E; Murphy, Marie; Griffiths, Frances
In the past decade, there has been a groundswell of interest in the use of mixed-methods approaches to conduct research in the health sciences. However, there remains a paucity of diverse teaching materials, curricula and activities to support the continued expansion of education and innovation in mixed-methods research. Here, we report the development and evaluation of an open-space learning activity and tool to aid teaching the concept of synthesis in mixed-methods research. We detail the iterations of the teaching activity and tool as they were developed, we report student feedback, and we discuss the utility of the activity and tool for introducing the concept of synthesis in mixed-methods research within health science and related fields.